Evidential weight of recent and delayed complaint in sexual assault trial proceedings - Mohamad Yunus, Mohamad Ismail (LexisNexis Malaysia Sdn. Bhd., 2016)
A failure to report sexual assault immediately after it occurred has evolved into a presumption of fabrication on the part of the complainant. This rule was based on 'the belief that a sexual assault complainant could only be believed if she could demonstrate she had publicly denounced the perpetrator, sexual assault com-plainants became a special category of witness whose credibility could be boosted by evidence of recent complaint'. Complaint evidence is a type of prior consistent statement, which is given by a witness or the complainant about when the complainant made their first report of sexual assault. The recent common law complaint rule only allows this type of evidence to be relevant and admissible if the complaint was made at the first reasonable opportunity after the alleged sexual assault. Further, it is only relevant and admissible for credibility purposes, that is, to bolster the credit of the complainant. The evidential rules as applied to sexual assault cases have been and remain a cause for some concern. This article will focus on the evidential value relating to the relevancy and admissibility of recent and delayed complaint rule at the trial proceedings for sexual assault.1